The use of facebook for administration and pedagogy purposes : a - toumi, hocine (Journal of Social Sciences and Humanities, 2025)
This study examines the use of Facebook by professors and students at the University of Mouloud MAMMERI of Tizi Ouzou in Algeria. This study is the first of its kind to explore the uses of Facebook in the Algerian higher education sector. We adopted a descriptive approach, using questionnaires and interviews to collect data. This approach is the most appropriate for investigating the subject in question. The theoretical framework underlying this research is the Theory of Uses and Gratifications, an important qualitative approach that has introduced a paradigm shift in modern communication studies from the 1970s.